Reconstructing fluid-flow events in Lower-Triassic sandstones of the eastern Paris Basin by elemental tracing and isotopic dating of nanometric illite crystals. (1st March 2016) - Blaise, Thomas; Clauer, Norbert; Cathelineau, Michel; Boiron, Marie-Christine; Techer, Isabelle; Boulvais, Philippe
Abstract: Lower- to Middle-Triassic sandstones from eastern Paris Basin were buried to a maximum depth of 2500 m at a paleo-temperature of about 100 °C. They contain extensive amounts of authigenic platy and filamentous illite particles similar to those reported in reservoirs generally buried at 3000 to –5000 m and subjected to temperatures of 120 to –150 °C. To evaluate this unexpected occurrence, such sandstones were collected from drill cores between 1825 and 2000 m depth, and nanometric-sized sub-fractions were separated. The illite crystals were identified by XRD, observed by SEM and TEM, analyzed for their major, trace, rare-earth elements and oxygen isotope compositions, and dated by K–Ar and Rb–Sr. Illite particles display varied growth features in the rock pore-space and on authigenic quartz and adularia that they postdate. TEM-EDS crystal-chemical in situ data show that the illite lath/fiber and platelet morphologies correspond at least to two populations with varied interlayer charges: between 0.7 and 0.9 for the former and between 0.8 and 1.0 for the latter, the Fe/Fe + Mg ratio being higher in the platelets. Except for the deeper conglomerate, the PAAS-normalized REE patterns of the illite crystals are bell-shaped, enriched in middle REEs. Ca-carbonates and Ca-phosphates were detected together with illite in the separates. These soluble components yield 87 Sr/ 86 Sr ratios that are not strictly in chemical equilibrium with the illite crystals, suggesting successive fluids flows with different chemical compositions. The K–Ar data of finer <0.05 μm illite separates confirm two crystallization events at 179.4 ± 4.5 and 149.4 ± 2.5 Ma during the Early and Late Jurassic. The slightly coarser fractions contain also earlier crystallized or detrital K-bearing minerals characterized by lower δ 18 O values. The δ 18 O of the finest authigenic illite separates tends to decrease slightly with depth, from 18.2 (±0.2) to 16.3 (±0.2)‰, suggesting different but contemporaneous crystallization conditions deeper in the section. The illite platelets and filaments crystallized in changing physical–chemical crystallization conditions induced by fluids flows through the host-rock pore system. These flow events were probably driven by repetitive rifting episodes of the North Atlantic Ocean, although located several hundreds kilometers away from eastern Paris Basin, and/or by fracturing events in the nearby basement of the Vosges Massif. Complex relationships between geodynamical events, thermal anomalies, and advective fluids confirm that remote tectonic activities can impact quiescent basins, even if located far from tectono-thermal activities, by discrete and long-distance fluid flows.